THE ELECTRON MICROSCOPIC RESEARCH OF PAСLITAXEL-INDUCED RETINAL CHANGES IN THE EXPERIMENT - Dovga, N.Z. (World of Medicine and Biology, 2016)
Introduction. Recently new data have appeared considering eye complications such as maculopathia with blindness after taxane applications. [Murphy J.B. et al., 2010; Modi D. et al., 2013 ]. Blindness is caused by degeneration of photoreceptor cells. Objective of the research – to study the structure of the retina during the process of paclitaxel induced retinopathy development using electron microscopy method. Materials and methods. In the run of the experiment random bred white rats of mass 150-200 g (30 animals) were given an itraperitoneally injection of Paclitaxel, (Actavis, Romania) the dose being 2mg/kg of body weight 4 times every second day; the total dose was 8 mg/kg of body weight, according to R. S. Polomano et al. method [2001]. The control group of animals (15 animals) was given an intraperitineally injection of isotonic solution of sodium chloride of the equivalent volume. The research material was taken in 1, 7, 14, and 27 days, 2 and 3 months after the last injection of Paclitaxel, for electron microscopy research. Results of the research and discussion. First of all the experimental dynamics after 1-7 days an injection of Paclitaxel are characterized by changes at the outer segments of cones and rods in the photoreceptor layer. At the outer plexiform layer identified axodendritic synapses between axons of photoreceptor cells and bipolar dendrites and horizontal neurons – spherules, that contain different number of synaptic vesicles and has different dimensions. On the 15th day of the experiment there may be observed areas of the narrowing and widening on the longitudinal section of outer segments in rod cells. In some areas disk destruction with local plasmalemma destroying can be discovered. In the inner segment there is vacuole transformation of mitochondria and blur of plasmalemma. Cilium is in the state of destruction. In the outer nuclear layer, the neuron nuclei are in various stages of damage, caryopyknosis and caryorrhexis among them; the nuclei are osmiophilic, the euchromatin cannot be identified in them. In the cytoplasm of ganglion layer neurons, one can see vacuolar transformation of mitochondria and notice myeline-like figures. In 27 days, the pigmentocytes become distinguished by long processes localized near rods and penetrating deeply in photoreceptor retina layer; in their cytoplasm the melanosomes have various pigment quantity. Pigmentocytes processes often become interconnected forming a grid. Degenerative processes in photoreceptor neurons become extended. The newly formed capillaries with thickened basal membranes appear in the layer of nerve fibers. In 3 months after Paclitaxel administration, one can see melanosomes, mitochondria and many myeline-like figures in pigmentocyte cytoplasm. In the outer segments of photosensor cells, the disks are in different morpho-functional state. Neurons of other layers are degenerative. In the layer of nerve fibers, the newly formed capillaries become a typical phenomenon. Thus, Paclitaxel induces retina toxicity, which manifests itself by morphological electron microscopic changes in the retina. The photoreceptor neurons being most vulnerable, they are identified to undergo dystrophic and destructive changes, deformation, vacuolization and outer segments destruction. The cells of retina neuronic chain – bipolar and ganglionic – are karyopyknotic, swollen, having vacuolar transformation of mitochondria and degranulated endoplasmic reticulum. The two month’s experiment has shown that a characteristic feature of Paclitaxel effect is nerve fiber layer neovascularization.